Meta-Analysis the Effect of Nicotine Replacement Therapy on the Successful Smoking Cessation - Lina Eta Safitri; Agus Kristiyanto; Bhisma Murti (Masters Program in Public Health, 2021)
Background: About 23% of the world's population smokes, which includes 32% of men with the highest prevalence coming from Indonesia and 7% are women. East Asia and Southeast Asia have the highest smoking prevalence in the world at around 45%, while in Indonesia, the problem of smoking is a serious threat due to the increasing prevalence of smoking at 18 years of age from 7.2% to 9.1%. This study aims to analyze the magnitude of the effect of using NRT on the success of smoking cessation based on a number of previous similar studies. Subjects and Method: This research is a systematic review and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles through a journal database which includes: Google Scholar, PubMed, and Science Direct by selecting articles published in 2011-2020. Keywords used include: